Social capital and poverty among Chilean welfare recipients: a case study of poor women in the Chilesolidario Programme in Maipú, Chile - Pinilla, Veronica (2013)
This research examines the relationship between poverty and social capital, based on the experiences of current and former welfare recipients in the Chilesolidario Programme. Poverty is conceptualized as the lack of social relations that, acting persistently and permanently over time, restricts the transfer of economic and non-material resources to disadvantaged people. Qualitative research was carried out in Villa San Luis 3, Maipú, Chile, which included 42 interviews conducted with welfare recipients, social workers, local public administrators of the Programme, and experts and academics on poverty. Three aims are addressed in this research. Firstly, the study looks at the types of social relations enjoyed by participants within Villa San Luis 3 and outside it. This thesis contends that familial relations are the basis for social interactions. It finds that beneficiaries of the Programme maintain only a few social relations beyond the family, whilst friends, acquaintances and contacts do not have the capacity to help in creating better social networks for recipients. Secondly, this thesis investigates whether or not the Programme successfully enables people to reduce poverty. It shows that there are no significant differences between current and former beneficiaries in terms of social relations enjoyed, income received, or capacity to generate social capital, and therefore the programme does not produce an effect in the long-term. Thirdly, this thesis suggests that self-employment is of limited use in reducing poverty, because Chilesolidario participants do not demonstrate the use of this means to deal permanently with their every day needs, and such independent work is not useful in the long-term. Overall, this research tends to support Bourdieu's theory of social capital and social inequality, suggesting that poor people in Villa San Luis 3 engage in few social relations, and these do not produce or reproduce social capital so as to reduce poverty. In this respect, the Chilesolidario Programme is not an aid to reducing poverty, and seed capital is not an appropriate instrument to be used by a group of people without the skills or social relations required to maintain self-employment in the long-term.